2021
DOI: 10.1007/s10798-021-09701-6
|View full text |Cite
|
Sign up to set email alerts
|

Ninth-grade students’ perceptions on the design-thinking mindset in the context of reverse engineering

Abstract: Recently, design thinking has become recognized as a necessity for every student, especially when they engage in design-based learning, as a pedagogical approach to science, technology, engineering, and mathematics education. However, design-based learning is mostly based on forward engineering, in which students' design thinking can be nurtured by designing unknown solutions. Little is known about whether design thinking can be facilitated in the context of reverse engineering, when students learn from alread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…These findings align with previous research indicating that technology-based courses that emphasize hands-on learning yield higher design thinking scores compared to traditional teaching methods (Lin et al, 2020). Furthermore, prior studies have also demonstrated that students' design thinking performance improves when involved in design-based learning (Ladachart et al, 2022).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These findings align with previous research indicating that technology-based courses that emphasize hands-on learning yield higher design thinking scores compared to traditional teaching methods (Lin et al, 2020). Furthermore, prior studies have also demonstrated that students' design thinking performance improves when involved in design-based learning (Ladachart et al, 2022).…”
Section: Resultssupporting
confidence: 89%
“…Quantitative data were collected using a self-perception questionnaire called the Design Thinking Scale, developed by Ladachart et al (2022). This instrument assessed six indicators of students' design thinking competencies, including comfort with uncertainty and risks, human-centeredness, mindfulness of process and impacts, collaborative work with diversity, orientation to learning by making and testing, and confidence in using creativity.…”
Section: Research Instrumentmentioning
confidence: 99%
“…In Thailand, where this study was conducted, DT has gained increasing attention because of the STEM education policy. As Thai scholars, we also used Dosi et al's (2018) comprehensive list of aspects of DT to measure teachers' and students' perception of their DT (Ladachart, Ladachart, Phothong, & Suaklay, 2021;Ladachart, Cholsin, Kwanpet, Teerapanpong, Dessi, Phuangsuwan, & Phothong, 2021). While DT can be measured in several ways, measuring individuals' perceptions of their own DT using Likert-type surveys can 'provide insights about the extent they are able to think like designers' (Koh et al, 2015, p. 115).…”
Section: Design Thinkingmentioning
confidence: 99%
“…Therefore, a flipped classroom in elementary school would look different from one in high school (Gholami et al, 2023). From about 6 to 11 years old, roughly the years of primary or elementary school, children become proficient in basic skills such as reading, writing, and arithmetic, show interest in discovering and understanding their surroundings, and their personal control increases (Ladachart et al, 2022). Children are the most valuable human assets of any society and play a significant role in shaping the future of any country, but they can only fulfill this role properly if they are empowered with the necessary capabilities.…”
Section: Introductionmentioning
confidence: 99%